Optimalisasi Peran BUMDes dalam Pengembangan Ekowisata melalui Business Plan dan Penguatan Mental Usaha di Desa Paguyuban Kecamatan Way Lima Kabupaten Pesawaran - Sari Indah Oktanti Sembiring; Mega Metalia (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: The establishment of the Telaga Batu Putih BUMDes aims to participate in village development and provide services to the community in its management carried out by the village government and the community. The existence of the Telaga Batu Putih village-owned enterprises (BUMDes) is expected to be able to improve the village economy to create community welfare. The purpose of this study was to determine whether the role of the Telaga Batu Putih BUMDes was optimal for the welfare of the village community or not. Because BUMDes Margo Guyub has a set of apparatus that have worked fine, but the BUMDes has not optimally marketed its business units. Methodology/approach: This research is a qualitative research with a descriptive approach. The place in this study is in the Paguyuban village Kecamatan Way Lima, Kabupaten Pesawaran. Results/findings: The results showed that the Telaga Batu Putih BUMDes has played a role in improving the welfare of the community, but it has not been optimal in its implementation, the factors that become obstacles in running a business are limited human resources, weak managerial capacity and low capital. Conclusion: The government's role is needed to conduct socialization and provide training and assistance to the community regarding the management of the Telaga Batu Putih BUMDes so that it can be carried out properly and professionally.